Squid Catching Productivity with Cast Net at the Nusantara Kejawanan Fishing Port, West Java - Sentosa, Agus Arifin; Riyanto, Jagad Slamet; Hadi, Abdul; Suryandari, Astri; Putri, Didha Andini; Wahyuningsih, Sri; Kusumaningtyas, Dyah Ika; Hendrawan, Andika Luky Setiyo; Hedianto, Dimas Angga; Susilawati, Evi; Indriatmoko, Indriatmoko; Widarmanto, Nanang; Gumilang, Andi Perdana; Sudarto, Sudarto; Astuti, Iswari Ratna; Indrianto, Rachmat (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
The Nusantara Fishing Port (PPN) Kejawanan is located in the Lemahwungkuk District of Cirebon City. Cast nets are a widely used fishing gear for catching squid. This study aims to describe how cast nets are operated and to analyze variations in squid catch productivity per trip and per gross tonnage (GT) of the vessel. The method used was a survey method through direct observation and interviews to obtain technical data on fishing operations and catch results. Observations were made on seven (7) cast net vessels per month (n = 7 vessels/month) during the period January–March 2024. The results of the study show that during January–March 2024, the highest productivity value occurred in January at 7,349 kg/trip and the lowest value was 6,224 kg/trip in February. Meanwhile, the highest productivity per GT of vessel catch was in January at 183.73 kg/GT of vessel, and the lowest was in February at 121.02 kg/GT. This variation in productivity between months occurred in the context of the season and was related to a combination of technical operational factors and fishing environmental conditions.